2016
DOI: 10.1074/jbc.m115.708354
|View full text |Cite
|
Sign up to set email alerts
|

Thumb Site 2 Inhibitors of Hepatitis C Viral RNA-dependent RNA Polymerase Allosterically Block the Transition from Initiation to Elongation

Abstract: Replication of the hepatitis C viral genome is catalyzed by the NS5B (nonstructural protein 5B) RNA-dependent RNA polymerase, which is a major target of antiviral drugs currently in the clinic. Prior studies established that initiation of RNA replication could be facilitated by starting with a dinucleotide (pGG). Here we establish conditions for efficient initiation from GTP to form the dinucleotide and subsequent intermediates leading to highly processive elongation, and we examined the effects of four classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…The order Lomibuvir Ͼ GS-9669 Ͼ Filibuvir, observed in ranking the magnitude of the effects on ⌬% D, correlates with the potency of inhibition seen in kinetic studies (11).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The order Lomibuvir Ͼ GS-9669 Ͼ Filibuvir, observed in ranking the magnitude of the effects on ⌬% D, correlates with the potency of inhibition seen in kinetic studies (11).…”
Section: Resultsmentioning
confidence: 99%
“…A companion paper (11) showed that NNI2s inhibit RNA replication by slowing the transition from initiation to elongation, implying long range structural effects of NNI2s on enzyme dynamics. To gain insights into the underlying molecular basis for this allosteric inhibition, we used HDX kinetics to quantify changes in enzyme dynamics in the absence and presence of three different NNI2s.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations